IMPACT OF ORAL DISEASES AND ORAL HEALTH-RELATED CONDITIONS ON QUALITY OF LIFE. - Babayeva N.M (TADQIQOTLAR.UZ, 2024)
Abstract. Oral health-related quality of life (OHRQoL) is a novel concept that has  evolved  over  the  past  two  decades.  Information  on  OHRQoL  gives  better understanding about feelings and perceptions on an individual level. It also helps us to understand the impact of oral health on the lives on the patients and their family. It is now well documented that oral diseases and conditions impact people’s life. Some of the oral diseases/conditions like caries, dental fluorosis, tooth loss, periodontal disease, dental injuries, oral cancer, dental anomalies, craniofacial disorders, and many more have got negative impact on QoL.